A GP worth staying for - Heaton, Louisa (Harlequin medical romance, 2021)
A second chance...with the new island doc? For widowed GP Owen Ledger, the arrival of his replacement, Dr. Lucy Childs, is step one on the road to a new life away from the island where he spent his marriage. Only as Owen hands over the practice to warmhearted Lucy, he starts to see everything through fresh eyes. Could Lucy be the final step to a second chance and show Owen that he does belong on the island--with her?